AB0116 Sirt-1 Activity in PBMC from Patients with Rheumatoid Arthritis. (10th June 2014) - Wendling, D.; Vidon, C.; Khan, K.A.; Guillot, X.; Godfrin-Valnet, M.; Abbas, W.; Toussirot, E.; Baud, L.; Prati, C.; Herbein, G.
Abstract : Background: Sirtuin 1 (Sirt1) is a nuclear enzyme from the class III histone deacetylases (HDACs) modulating gene expression, involved in the regulation of various biological processes (cell survival, apoptosis, gluconeogenesis, adipogenesis, lipolysis), local and systemic inflammation, as well as in bone and cartilage remodeling. Sirt-1 reduces pro inflammatory cytokines release. Objectives: The main objective of the study was to evaluate Sirt1 activity in PBMC by venous blood aspiration in rheumatoid arthritis (RA) patients, compared to those of control patients, and to analyze the relationship between Sirt1 activity, disease activity and production of mediators of inflammation and cytokines (TNFalpha, IL-6, IL-8) by the cells, before and after ex vivo treatment with a Sirtuin activator, resveratrol. Methods: A prospective and comparative monocentric study was performed in order to compare the activity of Sirt1 in patients with RA (according to ACR criteria) and controls. Disease activity was assessed by DAS28 (ESR) and CRP. PBMC were isolated from venous blood, and Sirt1 activity was evaluated from cytoplasmic and nuclear compartments using a fluorometric assay (SIRT1 fluorimetric kit, BML-AK-555, Enzo Life Sciences, Villeurbanne, France) at the 15 minutes point. Culture supernatant levels of TNF alpha, IL-6, IL-8 were quantified before and after resveratrol (1 μmol and 5 μmol) ex vivo treatment, with commercial kits (Quantikine Kits, R&D Systems, Minneapolis, MN). Statistical analysis used Wilcoxon and t tests; significance: p less than 0.05. Results: Twenty two patients with RA (age 55±12 years, meanDAS28: 4.27;disease duration 15±10 years; 75% ACPA +; mean CRP: 12.7 mg/l) and 18 controls (age 54±13 years) were included. No differences were found in cytoplasmic or nuclear Sirt1 activity between patients and controls. Cytoplasmic and nuclear Sirt1 activity were correlated in patients and controls. Sirt1 activity (nuclear and cytoplasmic) was not correlated with DAS28, CRP or ESR, but cytoplasmic Sirt-1 activity was correlated to baseline IL-6 (p=0.02) and baseline TNF (p=0.04) in RA and controls, but not with IL-8. Sirt1 activity (cytoplasmic and nuclear) was lower in RA ACPA+ compared to ACPA neg, and nuclear activity was higher in patients treated with corticosteroids. After resveratrol treatment, no changes in TNF, IL-6 or IL-8 levels were found, Conclusions: Sirt1 activity (cytoplasmic and nuclear) from PBMC was not different between RA patients and controls, nevertheless, the correlation in RA with Sirt1 activity and TNF and IL-6 levels, as well as reduced Sirt1 activity in ACPA + patients suggest an implication of this epigenetic regulation in RA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1584